Relationship between education and production value of small and medium family farms in Poland - Polcyn, Jan; Stępień, Sebastian; Kwiliński, Aleksy (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
Scientific reports indicate a very important role of human capital manifesting itself as a significant impact on the gross domestic product. Since agriculture creates a significant part of the gross domestic product, it may be assumed that human capital significantly influences production in this sector of the economy. A significant role in the global agricultural production is played by small and medium family farms, in particular, their important role in maintaining biodiversity and providing traditionally produced food. Taking into account the above dependencies, the aim of the study was to verify the influence of the education of the owners of small and medium farms on the production value. Small and medium family farms in Poland have been analysed. After analysing a variety of definitions, the qualification criteria for this group of farms included the area of the farm (up to 20 ha), the value of standard production (up to 25 thousand EUR), and the share of own labour involved in agriculture (at a minimum level of 75%). The data for analyses were obtained through surveys conducted on a sample of 710 farms from Poland. The surveys were carried out in 2019. The following variables were included in the analysis: farm area, total farm output value per ha and per farm member, and a synthetic measure of human capital. The TOPSIS-CRITIC method was used to determine the synthetic measure of human capital, and the following were included in the said measure: age of the farm manager, participation in continuing education, and education of the farm manager. The analysed farms were divided into two classes according to their education, i.e. one class consisted of farms where the owner had a university degree and the other class consisted of farms where the owner had a secondary or lower secondary education. Contrast analysis was conducted between the determined classes. The analyses conducted in this study indicate a significant relationship between the farm owner's education and the value of total farm production per ha and per farm member. A more favourable value of total farm production per ha and per farm member was found in farms where the manager had a higher vocational education or master's degree. This difference should not be explained by the farm’s production scale and size when compared to the farms of a larger area with University educated farm owners, because the difference in area between the classes of these farms was too small.